Multiple-Description Lattice Vector Quantization For Image And Video Coding Based On Coincidings Similar Sublattices Of An - Akhtarkavan, Ehsan (2012)
Nowadays applications of multimedia communication are found everywhere. Digital communication systems deal with representation of digital data for either storage or transmission. The size of the digital data is a crucial factor for storage and error resiliency of the data is a crucial factor for transmission systems. Thus, it is required to have more efficient encoding algorithms in terms of compression and error resiliency. Multiple-description (MD) coding has been a popular choice for robust data transmission over unreliable network channels.